To be Excellent Society: Comparative Analysis between Western and Muslim Philosophers - Humaidi Hum AS (Ulumuna, 2016)
The western philosophers like Karl Marx believe that society is ontologically understood in terms of physical dimension only while the Muslim philosophers such as al-Fārābī, Nasīr al-Dīn al-Tūsī, Ibn Khaldūn and Murtaḍā Muṭahharī argue that it consists of physical and metaphysical or spiritual aspects. The structure of a society along with its development and orientation can be seen and explained by its physical and metaphysical aspects. Moreover, the perfection of a society is not only based on the fulfilment of its physical needs but also on the establishment of intellectual and spiritual needs. This article aims to discuss society through Islamic philosophy’s perspective with the elaboration of social science, the reality of a society, the structure of an ideal society and its development and orientation. DOI: http://dx.doi.org/10.20414/ujis.v20i1.823